Dynamic Release of Sediments Nitrogen in Shallow Lake with Strong Hydrodynamic Disturbance - Nie, Bei; Zeng, Yuhong; Zhang, Xiaofeng; Xue, Yingwen (Journal of Environmental Accounting and Management, 2026)
Nitrogen enrichment is a major problem for lakes and reservoirs, which may result in increased algae growth. Environmental factors, such as hydrodynamic disturbance, play an important role in the release of secondary pollution from sediments, especially in shallow lakes. In this study, the dynamic release of total nitrogen (TN) from sediments under different hydrodynamic conditions was investigated by conducting seven sets of laboratory experiments with a specialized apparatus. The TN, nitrate-nitrogen (NO_3-N) concentration in the overlying water and TN concentration in the sediment were measured simultaneously. Experimental results showed that the sediment nitrogen release was strongly affected by the hydrodynamic conditions, and the TN release amount increased greatly with enhanced hydraulic disturbance. Different with that under a constant shearing velocity, the release rate of TN was significantly influenced by the time-varying disturbance intensity, and the initial release process is crucial to the entire release. The massive resuspension of sediment arosed by strong hydrodynamic disturbance contributes to the high TN concentration in the water body, and the numerically calculated concentration of the suspended sediment has the same varying trend with the variation of TN concentration before reaching the equilibrium state. This relationship might be utilized to predict the release of TN under strong disturbance.